The European court of human rights, its judicial lawmaking and its impact on the case law of national courts - Гордєєв, Віталій Володимирович; Chernadchuk, T., Yasynok, D., Gordieiev, V., Klietsova, N., & Boiko, V (My University, 2022)
Abstract: The article examines the problem of legal qualification of the legal positions of the European Court of Human Rights. Various aspects of the functioning of the European Court of Human Rights in the context of the human rights protection system are considered. The article deals with the issue of the influence of legal positions on civil law. In addition, the possibility of judicial law-making is consistently proved. The existing approaches to understanding the nature of the legal position of the court are summarized. It is shown that the European Court of Human Rights, when interpreting certain provisions of the Convention for the Protection of Human Rights and Fundamental Freedoms, focuses on its own decisions made earlier. A distinction is made between the terms “legal position” and “decision of the European Court of Human Rights”.
Keywords: Convention for the Protection of Human Rights, International experience, European Court of Human Rights, Lawmaking, Legal position.